Optimisation of Financial Risk with the Aid of Hedging Tools - Jaroslav Slepecky (Communications - Scientific letters of the University of Zilina, 2002)
The paper deals with one of the possibilities of optimising the financial risk with the aid of hedging tools. The current risk does not represent a negligible danger of losses from financial operations for the companies making business in Eurodollars in the present conditions of big volatility of the Slovak crowns. The use of simple hedging tools allows eliminating of the risk of currency losses.